Alloy selective optical sorting of mixed post-consumer aluminum scrap streams - Mert Efe; Aashish Rohatgi; Qiang Dai; Brian Stapleton; Kate Rader; Albert L. Lipson; Jeffrey S. Spangenberger (Resources, Conservation and Recycling, 2025)

The utility of silicone wristbands in characterizing exposure to parabens found in commercial lotions - Jessica L. Levasseur; Kate Hoffman; Sharon Zhang; Heather M. Stapleton (Science of The Total Environment, 2025)

Children’s exposure to chemical contaminants: Demographic disparities and associations with the developing basal ganglia - Carina H. Fowler; Aaron Reuben; Heather M. Stapleton; Kate Hoffman; Nicholas Herkert; Lubna Barakat; Michael S. Gaffrey (Environmental Research, 2024)

Children's exposure to brominated flame retardants in the home: The TESIE study - Kate Hoffman; Xuening Tang; Ellen M. Cooper; Stephanie C. Hammel; Andreas Sjodin; Allison L. Phillips; Thomas F. Webster; Heather M. Stapleton (Environmental Pollution, 2024)

Chemical uptake into silicone wristbands over a five day period - Samantha M. Samon; Kate Hoffman; Nicholas Herkert; Heather M. Stapleton (Environmental Pollution, 2024)

Characterizing azobenzene disperse dyes and related compounds in house dust and their correlations with other organic contaminant classes - Kirsten E. Overdahl; Christopher D. Kassotis; Kate Hoffman; Gordon J. Getzinger; Allison Phillips; Stephanie Hammel; Heather M. Stapleton; P. Lee Ferguson (Environmental Pollution, 2023)

Measuring semi-volatile organic compound exposures during pregnancy using silicone wristbands - Samantha Samon; Nicholas Herkert; Akhgar Ghassabian; Hongxiu Liu; Stephanie C. Hammel; Leonardo Trasande; Heather M. Stapleton; Kate Hoffman (Chemosphere, 2023)

PFAS levels in paired drinking water and serum samples collected from an exposed community in Central North Carolina - Samantha M. Hall; Sharon Zhang; George H. Tait; Kate Hoffman; David N. Collier; Jane A. Hoppin; Heather M. Stapleton (Science of The Total Environment, 2023)

Brominated flame retardants and legacy organochlorines in archived human placenta samples: Sex differences, temporal analysis and associations with infant birth weight. - Matthew Ruis; Kate Hoffman; Heather M. Stapleton (Chemosphere, 2023)

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Organophosphate Esters: Are These Flame Retardants and Plasticizers Affecting Children’s Health? - Brett T. Doherty; Stephanie C. Hammel; Julie L. Daniels; Heather M. Stapleton; Kate Hoffman (Current Environmental Health Reports, 2019)

Establishing Representative No‐Take Areas in the Great Barrier Reef: Large‐Scale Implementation of Theory on Marine Protected Areas - LEANNE FERNANDES; JON DAY; ADAM LEWIS; SUZANNE SLEGERS; BRIGID KERRIGAN; DAN BREEN; DARREN CAMERON; BELINDA JAGO; JAMES HALL; DAVE LOWE; JAMES INNES; JOHN TANZER; et al. (Conservation Biology, 2005)
The Great Barrier Reef Marine Park, an area almost the size of Japan, has a new network of no‐take areas that significantly improves the protection of biodiversity. The new marine park zoning implements, in a quantitative manner, many of the theoretical design principles discussed in the literature. For example, the new network of no‐take areas has at least 20% protection per “bioregion,” minimum levels of protection for all known habitats and special or unique features, and minimum sizes for no‐take areas of at least 10 or 20 km across at the smallest diameter. Overall, more than 33% of the Great Barrier Reef Marine Park is now in no‐take areas (previously 4.5%). The steps taken leading to this outcome were to clarify to the interested public why the existing level of protection was inadequate; detail the conservation objectives of establishing new no‐take areas; work with relevant and independent experts to define, and contribute to, the best scientific process to deliver on the objectives; describe the biodiversity (e.g., map bioregions); define operational principles needed to achieve the objectives; invite community input on all of the above; gather and layer the data gathered in round‐table discussions; report the degree of achievement of principles for various options of no‐take areas; and determine how to address negative impacts. Some of the key success factors in this case have global relevance and include focusing initial communication on the problem to be addressed; applying the precautionary principle; using independent experts; facilitating input to decision making; conducting extensive and participatory consultation; having an existing marine park that encompassed much of the ecosystem; having legislative power under federal law; developing high‐level support; ensuring agency priority and ownership; and being able to address the issue of displaced fishers.